2022
DOI: 10.3389/fmicb.2022.968304
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of oral squamous cell carcinoma associated oral microbiome

Abstract: The intersection between the human oral microbiome and oral health is an emerging area of study which has gained momentum over the last decade. This momentum has motivated a search for associations between the oral microbiome and oral cancer, in hopes of identifying possible biomarkers that facilitate earlier diagnosis and improved prognosis for patients with that disease. The present study examined the relationship between the microbiome in the human oral cavity and oral squamous cell carcinoma (OSCC). We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…This genus comprises opportunistic pathogens that were first isolated from the upper layers of the atmosphere but also reside in soil ( 60 ). A systematic review and meta-analysis conducted by Peter et al on the oral SCC-associated microbiome found that Janibacter was more abundant in the control population than in the oral SCC population ( 61 ). Herpetosiphon is a genus comprised of at least four species known for their filamentous gliding motility and ability to prey on other microbes including several staphylococcal species ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus comprises opportunistic pathogens that were first isolated from the upper layers of the atmosphere but also reside in soil ( 60 ). A systematic review and meta-analysis conducted by Peter et al on the oral SCC-associated microbiome found that Janibacter was more abundant in the control population than in the oral SCC population ( 61 ). Herpetosiphon is a genus comprised of at least four species known for their filamentous gliding motility and ability to prey on other microbes including several staphylococcal species ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peptostreptococcus and Filifactor were two of the genera shared between SCC_PL and SCC samples ( Table S5 ). Peter et al found that these two genera were abundant in oral SCC patients compared to the control population ( 61 ). Filifactor species, F. villosus and F. alocis, are pathogenic biofilm-generating bacteria that are positively correlated with canine and human periodontal disease ( 64 , 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown substantial differences in bacterial diversity and the relative abundance of certain bacteria in the oral flora of cancer patients compared to controls with high-throughput sequencing techniques [ 74 ]. Several studies have reported the possibility of using oral swabs to analyze the microbiota on the surface of OSCC lesions and have found an increase in microbial diversity (alpha diversity) [ 75 ]. In addition, there was an increase in Fusobacterium and a decrease in Streptococcus at the tumor site since some authors examined tissue biopsy samples from OSCC patients and found that Prevotella , Corynebacterium , Pseudomonas , Deinococcus , and Noviherbaspirillum were enriched in tumor tissues, while Actinomyces , Sutterella , Stenotrophomonas , Anoxybacillus , and Serratia were significantly less abundant.…”
Section: The Role Of Oral and Vaginal Microbiota In Viral Oncogenesismentioning
confidence: 99%
“…However, inconsistencies are observed for microbes such as Streptococcus, Actinomyces and Prevotella, meaning that it is necessary to identify a consensus microbiota signature for HNSC [27,31,32,35,36]. Previous systematic reviews have tried to identify and describe the dysbiosis in HNSC using processed [37][38][39][40][41][42][43] or re-analysed [44] data from studies containing heterogeneous HNSC sample types such as saliva, swab, oral rinse and tissues. Differences in sequencing techniques, data processing and sample types among the original studies were mostly unaccounted for in these reviews and may limit interpretation of the overall findings.…”
Section: Introductionmentioning
confidence: 99%